TATALAKSANA OTITIS MEDIA SUPURATIF KRONIS PADA AKTIVITAS MASYRAKAT DI DAERAH KEPULAUAN b - Lale Aqmarina Awanis; I Gusti Ayu Trisna Aryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Chronic suppurative otitis media or CSOM is an inflammatory process in the middle ear cavity and mastoid process. CSOM is the cause of death for 50,000 children under five per year. The prevalence of chronic suppurative otitis media or CSOM worldwide is around 65-330 million people with otorrhoea and 39-200 million people, 60% of whom have decreased hearing function. Several things are known to increase the chance of chronic suppurative otitis media, including eustachian tube disorders, history of recurrent acute otitis media (AOM), chronic effusion otitis media, otitis media in infants, poor hygiene, passive smoking, malnutrition or immunodeficiency and urinary tract infections. repeated upper breaths. Management that can be done in CSOM can be in the form of aural irrigation, aural toilet, medical therapy, and antibiotic therapy. CSOM can cause complications to the cranial part. The purpose of writing this article is as a learning material for writers about the management of chronic suppurative otitis media in community activities in the archipelago.